Analisis kesulitan belajar dalam mata pelajaran IPS pada peserta didik kelas iv di sekolah dasar - Ajeng Tri Utami; Hadi Mulyono; Siti Istiyati (Didaktika Dwija Indria, 2021)
This research aims to describe the learning difficulties in social science of fourth grade students at Soropadan elementary school. The research data collected through document study analysis, interviews, and documentation. Data analysis used interactive analysis model by Miles and Huberman. Results of the data analysis showed that students experienced difficulties in material diversity in Indonesia, natural resources, economic activities, jobs, and kingdoms during the Hindu, Buddhist, and Islamic periods. Form of learning difficulties was difficult to understand the subject matter or the assignment and forgot easily after learn. Difficulties occured because students through that there was a lot of social science material so that it had an impact on incomprehension, lack of interest in social science lessons, lack of parental assistance while learning, limited learning resources, implementation of learning was not going well. Efforts were made to overcome the learning difficulties of social sciences: teacher observed the learning process and outcomes of students, allowed the students to find information in internet, parents thought their children to read materials, include their children to tutoring, students reread materials, asked the parent, and look for information in internet. This research can be used as a guide in minimizing learning difficulties of social science.Keywords: learning difficulties, social science, causative factor, effort, and elementary school